2016
DOI: 10.1111/hdi.12399
|View full text |Cite
|
Sign up to set email alerts
|

Both pelvic radiography and lateral abdominal radiography correlate well with coronary artery calcification measured by computed tomography in hemodialysis patients: A cross‐sectional study

Abstract: Introduction Lateral abdominal radiograph is suggested as an alternative to coronary artery computed tomography (CT) in evaluating vascular calcification. Simple scoring systems including pelvic radiograph scoring and abdominal scoring system were utilized to study their correlation with coronary artery calcification. Methods In 106 MHD patients, coronary artery CT, lateral abdominal, and pelvic radiograph were taken. The Agatston scoring system was applied to evaluate the degree of coronary artery calcificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Many noninvasive methods have been developed to detect VC and quantitate its severity. Plain radiography, the simplest technique, does not provide sufficient sensitivity and is not used for determining the amount of calcification. Sensitive methods for accurate assessment of calcification, especially in the coronary artery, include electron‐beam computerized tomography and multislice spiral computed tomography, the latter of which is fairly newer .…”
Section: General Considerations On Vascular Calcificationmentioning
confidence: 99%
“…Many noninvasive methods have been developed to detect VC and quantitate its severity. Plain radiography, the simplest technique, does not provide sufficient sensitivity and is not used for determining the amount of calcification. Sensitive methods for accurate assessment of calcification, especially in the coronary artery, include electron‐beam computerized tomography and multislice spiral computed tomography, the latter of which is fairly newer .…”
Section: General Considerations On Vascular Calcificationmentioning
confidence: 99%
“…Furthermore, the primary exposure of interest, whether intima or medial type of calcification could not be differentiated as correctly pointed out by the authors. 1 Could these facts explain the different outcomes described in both important studies published by the authors? 1,2 Furthermore, could different types of vascular calcification (Vc) correlate with significantly different coronary artery calcification (CAc) scores and possibly mortality?…”
Section: Dear Editormentioning
confidence: 99%
“…We praise Hong et al 1 for their excellent study demonstrating that both lateral abdominal and pelvic plain radiographs in hemodialysis patients are acceptable alternatives to computed tomography (CT) to efficiently evaluate vascular macro-calcification (Vmac) meaning that the presence of Vmac detected in series of simple X-rays has similar prognostic and therapeutic implications as modern expensive technologies. However, their earlier study found that coexistence of pelvic and hand artery macrocalcification rather than abdominal aorta calcification itself was associated with mortality in hemodialysis patients.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Increased Adragao score in hemodialysis patients was positively correlated with arterial stiffness, future CV events and mortality[33]. The degree of pelvic arterial calcification showed 67% sensitivity and 85% specificity for the prediction of CAC score ≥ 100 and above 80% sensitivity and specificity for the prediction of CAC ≥ 400[34]. …”
Section: Plain Radiographsmentioning
confidence: 99%